Simultaneous optical and dual-frequency radar observations of small mass meteors at Arecibo. (February 2019) - Michell, R.G.; DeLuca, M.; Janches, D.; Chen, R.; Samara, M.
Abstract: We present simultaneous optical and radar observations of meteors observed over the Arecibo radar in Puerto Rico. These observations were obtained during ∼ 24 h of radar time over 3 different nights in May 2012. The radar was operating in a dual-frequency mode at 430 MHz (UHF) and 46.8 MHz (VHF). The optical observations were made at 41 frames per second with an Andor Electron Multiplying CCD camera with a field of view of ∼ 6°, enabling the determination of accurate horizontal meteor velocities and optical light curves. There are varying detection sensitivities of the 3 different techniques (2 radar, 1 optical). The UHF radar is the most sensitive, resulting in a total of 8710 detected meteors during that period, while the VHF radar is significantly less sensitive—resulting in only 278 detected meteors. The optical observations are the least sensitive, resulting in a total of 178 detections. Of all of these meteors, only 19 were simultaneously detected by the 3 instruments. This paper focuses on the analysis of these 19 common events. The meteoroid masses determined from the optical light curves were found to be in the range of 20 μ g to 1.2 mg and did not correlate with the maximum Signal-to-Noise Ratio (SNR) of either radar. In addition, the UHF radar detected 5 out of these 19 meteors with far side-lobes, beyond the main-beam and first side-lobe. This indicates that a significant fraction of events detected by the UHF radar could be in far side lobes and therefore have significantly underestimated Radar Cross Sections (RCS), given the smaller backscattered powers received in the side lobes. Highlights: Simultaneous meteors can be observed with optics and both radars at Arecibo. The optically derived mass ranged from 20 micrograms to 1.2 mg. Most optical meteors were detected by the side-lobes of the UHF radar.